21st Mediterranean Conference on Control and Automation 2013
DOI: 10.1109/med.2013.6608881
|View full text |Cite
|
Sign up to set email alerts
|

Closed-form solution for absolute scale velocity estimation using visual and inertial data with a sliding least-squares estimation

Abstract: In this paper a method for the on-line absolutescale velocity estimation of a system composed of a single camera and of an inertial measurement unit is presented. The proposed formulation makes use of spherical image measurements acquired from at least three camera positions and inertial measurements to estimate the system velocity by solving also the absolute scale problem. A new multi-rate formulation based on a sliding least-squares estimation formulation is proposed, which is capable of providing the veloc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 27 publications
1
7
0
Order By: Relevance
“…They showed that the nonlinearity of the system mainly arises only from rotation drift. Recent results suggest that by assuming the orientation is known, VINS may be solved in a linear closed form [23]- [27]. It has been shown that both the initial gravity vector and the body frame velocity can be estimated linearly.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They showed that the nonlinearity of the system mainly arises only from rotation drift. Recent results suggest that by assuming the orientation is known, VINS may be solved in a linear closed form [23]- [27]. It has been shown that both the initial gravity vector and the body frame velocity can be estimated linearly.…”
Section: Introductionmentioning
confidence: 99%
“…This sliding window model applies to both linear initialization (Section V) and nonlinear optimization (Section VI). measurements in a sliding window [24]- [27] do not scale well to a large number of IMU measurements since they rely on double integration of accelerometer output over an extended period of time. Moreover, these closed-form approaches do not take the noise characteristic of the system into account, producing suboptimal results.…”
Section: Introductionmentioning
confidence: 99%
“…The vehicle initial position with respect to the fixed world frame is (−5, 5, 6) m, while the desired position is (0, 0, 1) m, thus requiring UAV's autonomous motion of at least 5 m. Note that no measure of the UAV translational velocity is used. The observer described by (10) provides an estimate of the velocity to controller (32) that generates desired thrust and attitude angles to the vehicle's native inner-loop block controller. The involved tuning gains are empirically set as follows: c 1 = 0.4, c 2 = 8, λ = 2, k 2o = 20, K 2o = 1e-2I 3 , and α 2 = 0.2.…”
Section: Simulation Resultsmentioning
confidence: 99%
“…For instance, one can set Γ = −(c 3 + c 1 c 2 )δ 3 , with c 3 being a positive control gain. In both the simulations and real-hardware experiments presented in the following, the vehicle is controlled with command (32) and (10). The visual controller generates roll/pitch angles and thrust to the UAV autopilot, as presented in Section III-B.…”
Section: Angular Velocity As Control Inputmentioning
confidence: 99%
See 1 more Smart Citation